Synthesis and Antimycobacterial and Photosynthesis-Inhibiting Evaluation of 2-[(E)-2-Substituted-ethenyl]-1,3-benzoxazoles - Ales Imramovsky; Jan Kozic; Matus Pesko; Jirina Stolarikova; Jarmila Vinsova; Katarina Kralova; Josef Jampilek (The Scientific World Journal)
A series of twelve 2-[(E)-2-substituted-ethenyl]-1,3-benzoxazoles was designed. All the synthesized compounds were tested against three mycobacterial strains. The compounds were also evaluated for their ability to inhibit photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts. 2-[(E)-2-(4-Methoxyphenyl)ethenyl]-1,3-benzoxazole, 2-[(E)-2-(2,3-dihydro-1-benzofuran-5-yl)ethenyl]-1,3-benzoxazole and 2-{(E)-2-[4-(methylsulfanyl)phenyl]ethenyl}-1,3-benzoxazole showed the highest activity against M. tuberculosis, M. kansasii, and M. avium, and they demonstrated significantly higher activity against M. avium and M. kansasii than isoniazid. The PET-inhibiting activity of the most active ortho-substituted compound 2-[(E)-2-(2-methoxyphenyl)ethenyl]-1,3-benzoxazole was IC50 = 76.3 μmol/L, while the PET-inhibiting activity of para-substituted compounds was significantly lower. The site of inhibitory action of tested compounds is situated on the donor side of photosystem II. The structure-activity relationships are discussed.